2020
DOI: 10.1097/md.0000000000023111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between distance and near visual acuity in amblyopes

Abstract: To compare distant visual acuity (DVA) and near visual acuity (NVA) in amblyopia and evaluate if NVA can be used to diagnose amblyopia. A retrospective study was performed on 73 patients diagnosed with amblyopia based on DVA, by measuring their NVA and comparing the DVA and NVA. The NVA was measured by Snellen chart at 30 cm and the DVA was measured by Dr Hahn vision test chart at 5m. The patients’ age, type of amblyopia, spherical equivalent, the difference between spherical equivalent and the fell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…13 Likewise, in amblyopic eyes, some studies 14,15 have reported poorer visual acuity at near than at distance, but other studies are in disagreement with this. 16,17 The present study concurs with previous research showing a similar level of agreement between a near visual acuity measurement (using the Runge near card) and the ETDRS chart. 18…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13 Likewise, in amblyopic eyes, some studies 14,15 have reported poorer visual acuity at near than at distance, but other studies are in disagreement with this. 16,17 The present study concurs with previous research showing a similar level of agreement between a near visual acuity measurement (using the Runge near card) and the ETDRS chart. 18…”
Section: Discussionsupporting
confidence: 91%
“… 13 Likewise, in amblyopic eyes, some studies 14 , 15 have reported poorer visual acuity at near than at distance, but other studies are in disagreement with this. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…There were some studies in this eld with controversy ndings. Similar to our study, Chun 12 in a retrospective study on 73 amblyopic patients (4-30 years) showed that the NVA was 0.24 log MAR better than the DVA. The difference between the DVA and NVA was not affected by age, type of amblyopia, spherical equivalent, and PD.…”
Section: Discussionsupporting
confidence: 91%
“…40 patients had strabismus with the mean size of 6.9 ± 14.7 prism diopter. 19 subjects were esotropic with the mean size of 25.6 ± 18.9 PD (10-70) and 17 patients had exotropia with the mean size of 32.2 ± 18.8 PD (10-65), and 4 of them had vertical strabismus with the mean size of 12.5 ± 4.5 PD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). While the mean distance visual acuity of our subjects was 0.39 ± 0.30 log MAR, the mean near visual acuity was 0.30 ± 0.32 log MAR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation